Analysis Of Quality Of Service Using The Swot Method At Pertamina Of Ihc Dental And Oral Poly Clinic In Jakarta - Syamsurizal (International Publisher (YAPENBI), 2023)
The purpose of this study was to analyze the quality of service using the SWOT method at the dental and oral clinic of the Pertamina IHC Clinic in Jakarta. The method used in this study uses a qualitative SWOT analysis model. The results of the study are the results of the SWOT strategy analysis, 1) Strength opportunities (SO) strategy, namely implementing service standards and improving the quality of existing services, increasing consumer confidence, expanding the target market. 2) Weaknesses opportunity (WO) strategy, namely completing medical equipment and supply of goods. 3) Strength threat (ST) strategy, namely developing competitiveness, increasing the response of health workers, continuing to provide the best service in serving patients. 4) Weaknesses threat (WT) strategy, namely paying attention to patient comfort, equipping equipment and fittings to support service quality, immediately do digitalization so that it is easier for employees to work